Community Policing Sebagai Bentuk Pengendalian Sosial - Monica Margareth (Deviance Jurnal kriminologi, 2017)
The Culture of Control aims to describe crime control and cultural practices that give rise to crime. The anchor of this form of social control is an institution that handles crime, danger, delinquency and other social problems, including the criminal justice system, health system, immigration and border controls, social welfare systems and urban planning authorities. Controlling crime is one of the main responsibilities of the police. More specifically, fighting crime in society. In other words, the community hopes for a police figure who is suitable or in accordance with his community. This also leads to the growth of various demands and expectations of the community towards police performance. The police and the community are two strong ministers. Because the police came from the community. While on the other hand, the community is needed by the police because it is indeed where the work is done. For all intents and purposes, community policing in the 1990s replaced professional police in 1960 as a crime control paradigm. As an ideology and philosophy, community policing is putting people in control of their own environment. Community policing is a paradigm based on the assumption that a collaborative approach between the police and the community will facilitate an informal social control mechanism to manage risk and prevent crime. Therefore, crime control is the responsibility of a number of social actors as citizens are encouraged to be involved in facilitating targeted actions with the police by identifying areas where collective risk is considered high and by facilitating crime control practices.